Review of Outcomes after Diagnosis of Malignancy in Kidney Transplant Patients: UNOS Database - Het Patel; Nikhil Agrawal; Voravech Nissaisorakarn; Ridhi Gupta; Francesca Cardarelli (Transplantology, 2021)
Malignancy is the third major cause of death among transplant recipients. Patient and kidney transplant outcomes after the diagnosis of malignancy are not well described. We reviewed incidences and outcomes of colorectal, lung, PTLD, and renal malignancy after transplant among patients who received a transplant from January 2000 to December 2018 using the UNOS/OPTN database. Incidence of each malignancy was measured at 5 years and 10 years of transplant. The Kaplan–Meier curve was used for time-to-event analysis (graft and patient outcomes). Additionally, we sought to identify the causes of graft failure among these recipients. We found that 12,764 (5.5%) patients suffered malignancy, excluding squamous and basal cell skin carcinoma after transplant. During the first 5 years of transplant, incidence of colorectal, lung, PTLD, and renal malignancies was 2.99, 9.21, 15.61, and 8.55 per 10,000 person-years, respectively. Rates of graft failure were 10.3%, 7.6%, 19.9%, and 18.8%, respectively, among these patients at 5 years. Mortality rate was highest among patients who suffered lung malignancy (84%), followed by colorectal (61.5%), PTLD (49.1%), and renal (35.5%) at 5 years after diagnosis of malignancy. In conclusion, kidney transplant recipients diagnosed with lung malignancy have the lowest graft survival, compared to PTLD, colorectal, and renal malignancy. PTLD has the highest incidence rate in the first 5 years of transplant.